2020
DOI: 10.1039/c9ee02380a
|View full text |Cite
|
Sign up to set email alerts
|

Karst landform-featured monolithic electrode for water electrolysis in neutral media

Abstract: The development of cheap and efficient electrodes for water splitting is an ongoing challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(76 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…This indicated that photocorrosion was suppressed with the addition of Fe 2+ in the electrolyte. The initial increased current density after adding Fe 2+ can be ascribed to that ferric ions were incorporated into the surface of NiOOH OEC layer, which was favorable to the electrocatalytic activity and photoelectrochemical performance . This was consistent with Choi et al.…”
Section: Figuresupporting
confidence: 84%
“…This indicated that photocorrosion was suppressed with the addition of Fe 2+ in the electrolyte. The initial increased current density after adding Fe 2+ can be ascribed to that ferric ions were incorporated into the surface of NiOOH OEC layer, which was favorable to the electrocatalytic activity and photoelectrochemical performance . This was consistent with Choi et al.…”
Section: Figuresupporting
confidence: 84%
“…To drive a current density of 10 mA cm À2 , an overpotential of only 0.21 V is required for the Co 2 N 0.67 -BHPC, lower than Co 2 O 3 -BHPC (0.32 V). Also, the Tafel slope of the catalysts being regarded as one of the great tools to speculate the rate determining step of HER process [40]. As shown in Fig.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The SECM images indicate a high activity in the valley areas, which was conrmed by the topographical image as well. 215 The same electrocatalyst exhibited good activity towards the OER as well and this performance is attributed to the karst landform structure, which seems to ease the mass diffusion and to provide sufficient catalytic sites. 215 SECM was employed as well for the investigation of photogenerated hydrogen at a 1,2-dichloroethane/water (DCE/W) interface by Jedraszko et al 216 During the HER, decamethylruthenocene (DMRc) is formed as a by-product during the hydrogen evolution, and then serves as an electron donor, which permits a continuous HER.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 84%
“…215 The same electrocatalyst exhibited good activity towards the OER as well and this performance is attributed to the karst landform structure, which seems to ease the mass diffusion and to provide sufficient catalytic sites. 215 SECM was employed as well for the investigation of photogenerated hydrogen at a 1,2-dichloroethane/water (DCE/W) interface by Jedraszko et al 216 During the HER, decamethylruthenocene (DMRc) is formed as a by-product during the hydrogen evolution, and then serves as an electron donor, which permits a continuous HER. 216 The SECM setup consisted of two Pt electrodes separated by only 50 mm from each other through a liquid/liquid interface, in order to ensure an efficient generation of DMRc by DMRc + reduction.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 84%
See 1 more Smart Citation